COMPOSITION AND SERIES TYPE OF NICKELIFEROUS METAMAFIC ROCKS OF THE LOVNO DISTRICT, KOLA PENINSULA - Ivanov A.A.; Predovskiy A.A.; Kozlov N.Y. (My University, 1988)
The Lovno Lake copper-nickel sulfide deposit is in the northwestern part of the Lapland granulite belt. We sampled typical metanorite and metagabbro-norite from the Lovno Lake deposit, as well as metanorite fragments from the explosion breccias. The rocks studied, though comparatively high in SiO2 and MgO, contain persistently low concentrations of TiO2 and alkalies and have a relatively low mafic index. Therefore, they can be compared with derivatives of komatiite melts and regarded as intrusive rocks of komatiite series type.